Design and Evaluation of an IoT-Enabled ESP32 Photoplethysmography Monitor for Heart Rate and SpO₂ - Muhhammad Iyan Putra Pratama; Luthfan Hadi Pramono; Adi Kurniawan Saputro; Dian Neipa Purnamasari; Muttaqin Hardiwansyah (Jurnal Teknik Elektro dan Komputer TRIAC, 2025)
Cardiovascular disease (CVD) motivates affordable, continuous monitoring of heart rate and peripheral oxygen saturation (SpO₂). We present a single-MCU device using an ESP32 and MAX30102 photoplethysmography sensor that acquires heart rate and SpO₂ and streams data to a ThingSpeak dashboard. Performance was evaluated over four consecutive days under normal conditions, with five paired measurements per day against a clinically approved fingertip oximeter. Using all paired observations, the proposed design achieved low errors with RMSE = 0.84 bpm for heart rate and 0.59 percentage points for SpO₂, the maximum absolute error did not exceed 1 bpm or 1 pp, respectively. These results demonstrate end-to-end operation and good agreement with reference in resting conditions.